Social image concerns and welfare take-up - Jana Friedrichsen; Tobias König; Renke Schmacker (Journal of Public Economics, 2018)
Using a laboratory experiment, we present first evidence that social image concerns causally reduce the take-up of an individually beneficial transfer. Our design manipulates the informativeness of the take-up decision by varying whether transfer eligibility is based on ability or luck, and how the transfer is financed. We find that subjects avoid the inference both of being low-skilled (ability stigma) and of being willing to live off others (free-rider stigma). Using a placebo treatment, we exclude other explanations for the observed stigma effects. Although stigma reduces take-up, elicitation of political preferences reveals that only a minority of “taxpayers” vote for the public transfer.
Keywords: C91; D03; H31; I38; 330; Stigma; Signaling; Redistribution; Non-take-up; Welfare program